Acute hemorrhagic cerebral artery dissection: Characteristics and endovascular treatment. Issue 2 (April 2020) - Lv, Xianli; Yu, Jianjun; Zhang, Wei; Zhao, Xuelian; Zhang, Huifang
Objective: Acute hemorrhagic cerebral artery dissection may show a subtle stenosis and bulge on an angiogram, for which diagnosis and treatment are difficult. This report describes seven cases of acute hemorrhagic cerebral artery dissection treated by endovascular techniques. Patients and methods: From January 2018 to April 2019, seven patients (22–76 years old) were diagnosed with subarachnoid hemorrhage caused by cerebral artery dissection. Six patients were treated by low-profile visualized intraluminal support stent-assisted coiling and there was a sacrifice of the posterior cerebral artery in one patient. Cerebral angiography results were obtained immediately after intervention and at follow-up. Clinical outcome was evaluated by a modified Rankin Scale score. Results: Four dissections were angiographic changes of subtle stenosis and small bulges; three were apparent angiographic changes of stenosis or fusiform morphologies. All seven aneurysms were completely obliterated, a low-profile visualized intraluminal support stent was used in six patients and coil occlusion of the parent artery in one patient. Complications occurred in two cases of proximal posterior cerebral artery dissection. One bleeding complication was observed intra-procedure and one ischemic complication was observed after stent-assisted coiling. The angiographic and clinical follow-up was obtained at 3–8 months in five patients. Good recovery was achieved for six patients (modified Rankin Score 0); one patient who presented Weber syndrome caused by ischemic complication had a modified Rankin Score of two at 8 months follow-up. Conclusion: Hemorrhagic cerebral artery dissection may show subtle stenosis, small bulges or fusiform morphologies on angiograms. Treatment of proximal posterior cerebral artery dissection is challenging. Endovascular reconstruction with a low-profile visualized intraluminal support stent was effective depending on the angiographic morphology.